2013
DOI: 10.1182/blood-2012-08-451278
|View full text |Cite
|
Sign up to set email alerts
|

In vivo leukemogenic potential of an interleukin 7 receptor α chain mutant in hematopoietic stem and progenitor cells

Abstract: Key Points Gain-of function mutation of IL7Rα induces lymphoid leukemia as well as myeloproliferative disease. In vivo oncogenicity of mutant IL7Rα is influenced by the differentiation stage at which it occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Although C7R expressing CAR T-cells do not show sustained autonomous/antigen independent growth and survival in vitro (Figure 1H,I), the transgene is modified from a class of constitutively active IL7R variants expressed in 10% of pre-T-cell acute leukemias (26), potentially increasing the risk of unwanted expansion. However, expression of this mutant receptor per se is not oncogenic, and transformation only occurs in association with multiple other driver mutations (27).…”
Section: Resultsmentioning
confidence: 99%
“…Although C7R expressing CAR T-cells do not show sustained autonomous/antigen independent growth and survival in vitro (Figure 1H,I), the transgene is modified from a class of constitutively active IL7R variants expressed in 10% of pre-T-cell acute leukemias (26), potentially increasing the risk of unwanted expansion. However, expression of this mutant receptor per se is not oncogenic, and transformation only occurs in association with multiple other driver mutations (27).…”
Section: Resultsmentioning
confidence: 99%
“…13,14,16 Therefore, we next sought to determine whether CK2 is also required in the context of the signals elicited by mutant IL7R. We found that CK2 inhibition prevented constitutive signaling downstream from mutated IL7R in DND-41 T-ALL cells, 16 as determined by the levels of phosphorylation of Akt and STAT5 ( Figure 5A). Accordingly, CX-4945 induced DND-41 cell death in a time-and dose-dependent manner ( Figure 5B,C), which was associated with high levels of apoptosis ( Figure 5D).…”
Section: Ck2 Inhibition Abrogates Constitutive Signaling and Viabilitmentioning
confidence: 99%
“…Around 10% of pediatric T-ALL patients display IL7R gain-of-function mutations, which lead to constitutive activation of downstream signaling and subsequent promotion of cell transformation and tumorigenesis. [12][13][14][15][16] Casein kinase 2 (CK2) is a ubiquitously expressed serine/threonine kinase, that is involved in the regulation of numerous cellular processes (e.g. cell cycle, gene expression and proliferation), through the modulation of the crosstalk between multiple signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of the receptors may be clonal or subclonal, preserved or altered between diagnosis and relapse 7,[19][20][21] . Two mouse models suggest that under specific conditions, expression of CRLF2 and/or IL7RA may initiate BCP-ALL [22][23][24] . Nevertheless, the relevance of these models to human BCP-ALL is unclear, due to major differences in the role of both IL7 and TSLP signaling in B-cell development in humans.…”
Section: Introductionmentioning
confidence: 99%